2011
DOI: 10.1525/auk.2010.10069
|View full text |Cite
|
Sign up to set email alerts
|

Combining Stable-Isotope and Body-Composition Analyses to Assess Nutrient-Allocation Strategies in Breeding White-Winged Scoters (Melanitta fusca)

Abstract: Birds meet the energy and nutrient demands of egg formation by using dietary (exogenous) sources, somatic (endogenous) nutrients, or combinations of both. Therefore, understanding plasticity in resource acquisition and the allocation strategies that are used is important for predicting how ecosystem changes across a species' range could affect vital rates. Sources of egg nutrients have traditionally been assessed through analyses of body composition, but stable-isotope analysis has provided a new tool in cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…We found that annual population fluctuations of scaup and especially scoter were positively linked to spring snow cover duration, such that lower duck densities resulted after springs with short snow cover duration, in contrast to highly flexible breeding species like mallard. Scaup and scoters arrive on breeding areas at similar times with stored nutrients that could be used for reproduction (Esler et al ., ; DeVink et al ., ; DeVink et al ., ). In contrast to mallard and American wigeon, scaup and scoters delay breeding for up to several weeks before nesting, suggesting differences in responses to changes in snow cover duration among these species are related to diet or timing of breeding (Table ).…”
Section: Discussionmentioning
confidence: 97%
“…We found that annual population fluctuations of scaup and especially scoter were positively linked to spring snow cover duration, such that lower duck densities resulted after springs with short snow cover duration, in contrast to highly flexible breeding species like mallard. Scaup and scoters arrive on breeding areas at similar times with stored nutrients that could be used for reproduction (Esler et al ., ; DeVink et al ., ; DeVink et al ., ). In contrast to mallard and American wigeon, scaup and scoters delay breeding for up to several weeks before nesting, suggesting differences in responses to changes in snow cover duration among these species are related to diet or timing of breeding (Table ).…”
Section: Discussionmentioning
confidence: 97%
“…If individual classes of macromolecules are isotopically labelled, then researchers can make even finer distinctions about the vertical transfer of nutrients. Two studies used this approach to demonstrate that both lizards (Warner et al, ) and ducks (De Vink, Slattery, Clark, Alisauskas, & Hobson, ) provisioned eggs with proteins from recently ingested meals. In contrast, the egg lipids were derived exclusively from stored resources.…”
Section: Physiological Differences Between Invaders and Native Animalsmentioning
confidence: 99%
“…Related to this point is the potential use of compound-specific approaches only to trace nutrient allocation to eggs. Nonetheless, the recent study by DeVink et al (2011) that used both isotopic (d 15 N, d 13 C) models and conventional body composition analyses to model capital vs. income allocations to eggs by White-winged Scoters (Melanitta fusca) found good agreement between the two approaches for bulk protein, suggesting that the carnivore model is currently a reasonable approach.…”
Section: Tracing Nutrients To Reproductionmentioning
confidence: 99%